Healthcare professional perspectives on medication challenges in the post-stroke patient - Bell, Shauna; Kelly, Helen; Hennessy, Eva; Bermingham, Margaret; O’Flynn, Jennifer Raymy; Sahm, Laura J. (Frontiers in Pharmacology, 2023)
Medications play an essential role in the management of patients who have experienced a stroke. Despite the recognised importance and widespread availability of secondary prevention guidelines, Irish research has shown a continuous failure to meet secondary prevention targets upon discharge.While complex interventions involving healthcare professionals (HCPs) such as Speech and Language Therapists (SLT), Occupational Therapists (OT) and Pharmacists have been effective in combatting medication non-adherence, community multidisciplinary teams (MDTs) are not as well defined as in the acute setting, leading to wide variation in patient care. Therefore, this study aims to investigate the knowledge, attitudes, beliefs, and challenges faced by HCPs in the continuity of care post-discharge from a hospital stroke ward, and its impact on medication adherence.Semi-structured interviews and one focus group with HCPs were conducted, and data were analysed using Braun & Clarke's reflexive Thematic Analysis.Fourteen HCPs (6 Pharmacy, 4 SLT, 4 OT) participated in this study. Participants discussed their views under two main themes (i) continuity of care and (ii) medication adherence. Sub-themes observed regarding continuity of care include management and organisation, interpersonal continuity, and informational continuity. Themes generated which impact medication adherence post-discharge include condition-related factors, medication-related factors, systemic and HCP factors, and patientrelated factors.